FEATURES OF SEASONAL CARDIOVASCULAR MORTALITY IN WINTER IN RUSSIAN REGIONS WITH DIFFERENT CLIMATIC AND GEOGRAPHICAL CHARACTERISTICS - S. A. Boytsov; M. M. Lukyanov; A. V. Kontsevaya; A. D. Deev; Yu. A. Balanova; A. V. Kapustina; V. G. Klyashtorny; M. B. Hudyakov (Столичная издательская компания, 2015)
Aim. To study seasonal changes in cardiovascular mortality in winter in Arkhangelsk, Ivanovo and Saratov regions - Russian regions with different climatic and geographical characteristics.Material and methods. Comparison of mortality in Arkhangelsk, Ivanovo and Saratov regions in 2007-2012 in January-March, December and April-November was performed by multivariate analysis of variance. Significance of differences was assessed by t-test of analysis of variance using programme GLM of SAS system.Results. Significantly higher cardiovascular mortality in population of Arkhangelsk (by 12.0%), Ivanovo (by 13.4%) and Saratov (by 11.5%) regions, as well as higher overall death-rate, during January-March, December, compared with April-November (p<0.0001) were found. Cardiovascular mortality decreased from 2007 to 2012 by 32.4% and by 32.9% per year and per January-March, December, respectively (p<0.0001). Higher cardiovascular mortality in the cold months of the year persisted in 2007-2012 and was higher than mortality per whole year by 8-14%. This difference in mortality did not decrease significantly (p>0.05).Conclusion. These findings point out the necessity of elaboration and implementation of the measures to prevent a winter increase in mortality, including the prevention of negative impact on the population of lowtemperature air, seasonal prophylaxis of acute respiratory viral infection, influenza and its complications, pharmacologic and non-pharmacologic prevention of cardio-vascular complications.